2007
DOI: 10.1002/chin.200722002
|View full text |Cite
|
Sign up to set email alerts
|

Predictions of the Properties of Water from First Principles.

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 200 leading journals. To access a ChemInform Abstract, please click on HTML or PDF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
79
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(80 citation statements)
references
References 31 publications
1
79
0
Order By: Relevance
“…To assess how well a given water potential reproduces experimental virial coefficient we calculated the χ 2 value, defined as sum of errors of calculated values with respect to experimental data: bold-italicχbold2=T(bold-italicBbold-italiccalc(T)bold-italicBboldexp(T)bold2/|bold-italicBboldexp(T)|. As can be seen from Figure 6 and Table S4 POL3-LT water model reproduces well experimental data as a function of temperature, with χ 2 value 216, which is substantially better than the value of 288 obtained for high quality quantum mechanically derived polarizable CC-pol 43 water potential as a function of temperature (see Table S4 and Figure S6). The lowest χ 2 values are obtained for DA/DA-LT/ET (87.9) and NDA/NDA-LT/ET (143) water potentials.…”
Section: Resultsmentioning
confidence: 76%
“…To assess how well a given water potential reproduces experimental virial coefficient we calculated the χ 2 value, defined as sum of errors of calculated values with respect to experimental data: bold-italicχbold2=T(bold-italicBbold-italiccalc(T)bold-italicBboldexp(T)bold2/|bold-italicBboldexp(T)|. As can be seen from Figure 6 and Table S4 POL3-LT water model reproduces well experimental data as a function of temperature, with χ 2 value 216, which is substantially better than the value of 288 obtained for high quality quantum mechanically derived polarizable CC-pol 43 water potential as a function of temperature (see Table S4 and Figure S6). The lowest χ 2 values are obtained for DA/DA-LT/ET (87.9) and NDA/NDA-LT/ET (143) water potentials.…”
Section: Resultsmentioning
confidence: 76%
“…Somewhat surprisingly, the resulting potential, named SDFT-5s, was found to be overall predicting the experimental properties better than SAPT-5s, although some VRT transitions were recovered significantly worse. 94 The outline of the paper is as follows. This indicated that inaccuracies of the two-body part are actually the major reason for the discrepancies with experiments seen in Ref.…”
Section: ͑Asp-s͒mentioning
confidence: 99%
“…11 This has led to the advent of several many-body PEFs for water in which the individual many-body terms in eqn (1) are tted to large sets of reference data calculated at the coupled cluster level of theory with single, double, and iterative triple excitations, i.e., CCSD(T), the current "gold standard" for molecular interactions. [12][13][14][15][16][17] Among existing many-body PEFs, it has been shown that the MB-pol PEF achieves great accuracy by integrating classical representations of many-body electrostatics, which correctly describe interactions at large molecular separations, with data-driven 2B and 3B terms represented by permutationally invariant polynomials (PIPs) that smoothly turn on as two and three water molecules, respectively, approach each other. [15][16][17] The MB-pol 2B and 3B terms, which were tted to large sets of CCSD(T) reference data calculated in the complete basis set (CBS) limit, effectively account for non-classical interactions (e.g., Pauli repulsion, charge transfer and charge penetration) arising in regions where the electron densities of individual water molecules overlap.…”
Section: Introductionmentioning
confidence: 99%